Global Infectious Diseases from April-June 2024: Periodic Analysis - Yi Luo; Guodan Li; Lin Lin; Dongliang Liu; Yinfu Sun; Taihan Li; Yufan Wu; Qi Xiang; Wenjin Yu; Dayong Gu (Zoonoses, 2024)
Infectious diseases pose a huge threat to human health. Human infectious diseases, especially infections originating from zoonotic or vector-borne sources, are an important global challenge. With the rising number of humans that engage in international travel, infectious disease outbreaks can spread rapidly across continents and borders worldwide. It is therefore important to monitor the transmission of infectious disease efficiently to prevent epidemics. We obtained surveillance data from the Shusi Tech Global Epidemic Information Monitoring System and comprehensively analyzed the timing and location of outbreaks in infected populations from April-June 2024.